Kreativitas terhadap Minat Berwirausaha Mahasiswa Keperawatan - Ernawati Ernawati (Jurnal Keperawatan Silampari, 2021)
This study aims to determine the effect of creativity on the entrepreneurial interest of Stikes Hang Tuah Tanjungpinang students. The method used in this study is a quantitative research method with a causal associative approach. The results of this study indicate that most of the respondents are female, as many as 84 students (75%). Most of the respondents aged 18-20 years were 102 students (91.1%). Bivariate analysis showed that creativity and interest in entrepreneurship obtained a large t-count value from the t-table (10,702 > 1.658) with a p-value of 0.000 <0.05. In conclusion, invention has a positive and significant effect on student entrepreneurship interest at Stikes Hangtuah Tanjungpinang. Keywords: Creativity, Interest in Entrepreneurship